ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN RISIKO - Christian Johanes Doi; Puji Harto (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to demonstrate empirically that product diversification, geographic diversification, company size, type of industry, leverage, profitability, and liquidity have significant effect on the risk disclosure of non-financial companies listed on the Indonesian Stock Exchange. The sample taken from companies’ annual reports from 2010 to 2012 with Purposive sampling techniques to obtain 61 firms.The analysis method in this study is descriptive statistics aimed to provide a description of the data of mean, standard deviation, variance, maximum, minimum. The study result indicates that product diversification, geographic diversification, industry type, Leverage and liquidity have effect on the risk disclosure. Whereas level of profitability has no effect on risk disclosure. The regression result shows only 29.3% of the company's disclosure risk is influenced by product diversification, geographic diversification, type of industry, leverage, profitability, liquidity. While 70.7% is influenced by other variables that are not observed in this study.The study results indicate that the independent variable such as Liquidity, profitability, industry type, product diversification, geographic diversification have no significant positive effect on risk disclosure, while the leverage has significant effect on the risk disclosure.